The Problems of Learning Media at University Amid Covid 19 Post New Normal in Indonesia - Ahmad Bustomi; Zuhairi Zuhairi; Rafiud Ilmudinulloh (Jurnal Ilmiah Iqra', 2021)
The Problems of Learning Media at University Amid Covid 19 Post New Normal in Indonesia. The aim of this research is necessary to be observed since Covid-19 has forced the education world to change its learning media. This study is conducted to equip the minimum research about learning amid pandemic Covid-19 specifically in Indonesian University. Meanwhile, this research focused on The Problems Of Learning At University Amid Covid-19 specifically at post-new normal. The new normal is a behavior change to run normal activities by complying with the health protocol for preventing the Covid-19 transmission.This research is field research. Interviewees in this research are postgraduate students who had undergone the learning in normal era at undergraduate’s program, and students conduct the postgraduate at new normal. at least, students discover what are the differences between those situations. The data collection method utilized interviews, observation, and documentation. Analysis which is utilized by a researcher is a model developed by Miles and Huberman. The steps consist of Data Reduction, Data Display, and Conclusion Drawing and Verification.The researcher has found some facts from this research such as learning at University amid covid-19 using the learning media that is commonly used like Whatsapp Group, Zoom Meeting, Google Meet, Google Classroom, Youtube, E-mail, Telegram. Besides, specific media used for learning in Indonesian University is not only common media but also using specific media that created by his own University. Second, using learning media amid Covid-19 post new normal shown several obstacles such as Lack of Understanding, Efficiency, High Cost, Environment Support, Media, Technologically backward.